Optimization operation strategy of electric boilers by mixed integer programming method in nickel production process - Djati, W S; Siswanto, N (IOP conference series. Materials Science and Engineering, 2021)
Nickel smelting process requires steam in the process of drying and calcining. Utilities Department is responsible for supplying steam either use electric boiler or fossil fuel. With fluctuations in fuel prices, limited electricity supply, boiler reliability, and government emission limits, it is a challenge for department utilities to produce steam. Planning and selection of boiler operations to produce steam to meet the needs of the smelting process are necessary in order to minimize operating costs and maintain boiler reliability in distributing steam. This condition makes mixed integer programming become the best method to solve the model. Mathematical models are used to determine boiler operations in the wet season and dry season by using mixed integer programming methods. In the wet season, boilers that use electricity can operate because electricity from hydropower is sufficient, although not fully the boiler can meet the steam needed. Whereas in the dry season boilers that use electricity cannot operate due to limited electricity supply generated from hydropower.